Developing Strategies for Msmes in Semarang City Using Swot Analysis - Handoyono, Rudi; Arbainah, Siti; Korawijayanti, Lardin; Pradana, Bagas Putra; Alfarizi, Musyafa (Moneta : Journal of Economics and Finance, 2026)
This study aims to formulate appropriate development strategies for Micro, Small, and Medium Enterprises (MSMEs) in Semarang City, with a focus on Tembalang, Pedurungan, and Banyumanik Districts. Using a descriptive quantitative approach, data were collected from 120 MSME respondents through structured questionnaires and analyzed using internal analysis, external analysis, and SWOT analysis. The findings show that MSMEs in Semarang City are positioned in Quadrant I of the SWOT matrix, indicating strong internal strengths and favorable external opportunities. The recommended strategy is an aggressive Strength-Opportunity (SO) approach, emphasizing the use of internal advantages—such as product quality and strategic location—to capture market opportunities. Practically, this study suggests that MSMEs should improve product quality, enhance brand visibility, build strong supplier relationships, and develop wider distribution channels. Future growth may also be supported through digital marketing and expansion along the supply chain. These insights can assist MSME actors and policymakers in designing more targeted and sustainable development efforts.